The Philippine National Innovation System: Structure and Characteristics - Epictetus Patalinghug (Philippine Institute for Development Studies (PIDS), 2003)
Industrial development requires technological capability in industry. National innovation system is anchored on the theory that industrial development requires technological capability in industry, and that exploitation of technology is most critical at the firm level. This paper describes the structure and characteristics of the Philippine national innovation system, and compares it with the American, Japanese, and German national systems of innovation. It concludes that the Philippine national innovation system must gear up to the requirements of a catch-up system to fit its institutions to its economic structure. This requires all the elements of the system to address the technology capability, adaptation, assimilation, and modification needs of a catch-up economy.
Keywords: 330; technology; innovation; capability; research and development (R&D); Innovation; Forschung; Wissenschaft; Industrieforschung; Technologiepolitik; Technologiepolitik; Philippinen